36.8k views
2 votes
What is the first step when rewriting y = 6x2 + 18x + 14 in the form y = a(x – h)2 + k? 16 must be factored from 18x + 14 x must be factored from 6x2 + 18x 6 must be factored from 6x2 + 14 6 must be factored from 6x2 + 18x

User Tishawna
by
5.4k points

2 Answers

6 votes
The first step is factoring out the 6 from the 6x2 + 18x. 
User Eaman
by
6.2k points
7 votes

Answer:

" 6 must be factored from
6x^2 + 18x "

Explanation:

We are given a equation as:


y=6x^2+18x+14

On expressing the given equation in terms of
y=a(x-h)^2+k

where h, k are real numbers; we get our quadratic equation as:


6(x-(3)/(2))^2+(1)/(2)

Here on comparing our equation with
y=a(x-h)^2+k we have :


h=(3)/(2) and
k=(1)/(2).

This means that we have to first factor out '6' from the term
6x^2+18x

User Theninjagreg
by
5.4k points